Sustainable Smart Factories: Digitalization’s Impact on Carbon Emission Reduction - Kasyap GNV, Maruthi (Digital Repository of Theses, 2025)
In the era of rapid digitalization, the industrial sector is progressively embracing smart factory technologies to enhance efficiency, productivity, and competitiveness. At the same time, sustainability and carbon footprint reduction have emerged as critical imperatives, driving industries to adopt environmentally responsible practices. This research investigates the role of digital transformation technologies in the development of smart factories and their influence on carbon footprint reduction. It explores the intricate relationship between digitalization and sustainability, offering a strategic framework for integrating these essential elements while navigating the complexities of disruptive technologies. This study employs a mixed methods research approach, incorporating qualitative and quantitative methodologies, including an extensive literature review, expert interviews, and survey based data collection. By analyzing empirical data, the research provides insights into the adoption and implementation of digital transformation technologies, assessing their effectiveness in reducing carbon footprints at various levels of industrial operations. The study identifies key digital innovations such as the Internet of Things, artificial intelligence, machine learning, digital twins, virtual reality/ augmented reality and blockchain and evaluates their impact on sustainability driven manufacturing processes. Findings from this research highlight the extent to which these technologies contribute to a carbon conscious industrial culture, enabling factories to optimize energy consumption, reduce waste, and enhance resource efficiency. The study further explores the challenges industries face in implementing digital solutions, including technological integration barriers, high initial investment costs, and workforce adaptability. It also discusses the role of policy frameworks and industry standards in accelerating the transition toward smart and sustainable factories. Additionally, this research provides strategic recommendations for industry practitioners, policymakers, and future researchers, addressing key implementation challenges associated with digital transformation technologies. It outlines best practices for overcoming obstacles, measuring carbon footprint reductions, and achieving long term sustainability goals. The findings contribute to a deeper understanding of how industries can leverage digitalization to balance technological advancements with environmental responsibility, ultimately shaping a future where smart factories drive both economic growth and sustainable development. By presenting a roadmap for harmonizing digitalization and sustainability in industrial operations, this study offers valuable insights into the evolving landscape of smart factories and their role in reducing the environmental impact of manufacturing.